Pengaruh Persepsi, Religiusitas, dan Pendapatan Masyarakat Muslim Kabupaten Sleman Terhadap Minat Berwakaf Uang - Suhasti, Wuri; Handayani, Lazinatul Febry; Winarno, Yulianto P (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
Potential for money waqf in Sleman Regency is around IDR 35 billion per month or IDR 420 billion per year. However, the magnitude of this potential is in fact still not being managed optimally. This is happen because public knowledge and education about mon`ey waqf is still very low. Money waqf is expected to be a solution to people's economic problems, because money waqf is considered to be more effective and efficient. This study aims to determine the effect of perception, religiosity, and income of the Muslim community in Sleman Regency on the interest in money waqf. This research is a quantitative study using multiple linear regression data analysis techniques with dummy variables as well as t test and F test. The data was obtained through distributing questionnaires to 175 respondents using purposive sampling technique. The results of this study indicate that, partially, the perception variable has a significant influence on the interest in money waqf. Meanwhile, the religiosity variable and the income variable did not have a partial significant effect on the interest in money waqf. Based on the results of the F test, the variables of perception, religiosity, and income have a simultaneous and significant effect on interest in money waqf, as evidenced by the value of sig. of 0.00 < 0.05.